A study on employees learning through communities of practices : case of Sabah Museum state department / Lediah Maun and Tracylyn Biug - Maun, Lediah; Biug, Tracylyn (2012)
Community of practice is defined as "a group of people who share an interest in a domain of human endeavor and engage in a process of collective learning that creates bonds between them" (Wenger, 2001, p. 1). It means the members in the CoP will: